1996
DOI: 10.2307/3432703
|View full text |Cite
|
Sign up to set email alerts
|

The Melatonin Hypothesis: Electric Power and Breast Cancer

Abstract: Breast cancer is a disease of modern life. As societies industrialize, risk increases, yet it is unclear which of the myriad changes coming with industrialization drives this increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 39 publications
1
45
1
1
Order By: Relevance
“…Furthermore, we observed that occupational exposure to extremely low frequency electromagnetic fields (EMF) was associated with an increased risk for uveal melanoma particularly among women [28]. EMF may indirectly increase the production of estrogen and prolactin via suppression of a release of melatonin from the pineal gland [36]. However, we did not observe an increased risk of uveal melanoma in either sex for pesticide exposure and occupational activities in farming or forestry.…”
Section: Exposurecontrasting
confidence: 56%
“…Furthermore, we observed that occupational exposure to extremely low frequency electromagnetic fields (EMF) was associated with an increased risk for uveal melanoma particularly among women [28]. EMF may indirectly increase the production of estrogen and prolactin via suppression of a release of melatonin from the pineal gland [36]. However, we did not observe an increased risk of uveal melanoma in either sex for pesticide exposure and occupational activities in farming or forestry.…”
Section: Exposurecontrasting
confidence: 56%
“…Suppression of melatonin exerts a pineal antigonadotropic effect which indirectly leads to an enhanced prolactin production in the pituitary gland as well as estrogen production in the ovaries. Again, this effect may increase the susceptibility to sex-hormone-related cancers, particularly among women [8,9]. In our own data we demonstrated a stronger effect on the risk of uveal melanoma after exposure to occupational ELF-EMF among women [10].…”
Section: Introductionmentioning
confidence: 54%
“…All these previous and the present data from Fischer rats indicate that power frequency MF exposure can exert a proliferative effect on different tissues in this strain. In the mammary gland, enhanced proliferation of epithelial stem cells increases the risk of malignant transformation, e.g., in response to chemical carcinogens such as DMBA [3, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…The disparity between the rates of breast cancer in industrialized and less-industrialized regions has led to many hypotheses, including the theory that exposure to light-at-night and/or electromagnetic fields may suppress melatonin and that reduced melatonin may increase the risk of breast cancer [2,3,4,5,6]. Exposures to extremely low-frequency electric and magnetic fields (MF) emanating from the generation, transmission, and use of electricity are a ubiquitous part of modern life.…”
Section: Introductionmentioning
confidence: 99%